2020
DOI: 10.29311/mas.v18i4.3456
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Leading the Project? A Comparative Study of Exhibition Production Practices at National Museums in Finland and the Baltic States

Abstract: This paper presents research into exhibition-production practices at five national museums of four Baltic Sea region countries. The focus is the changes wrought by the expansion of exhibition teams, and how researchers in the curatorial role perceive their position, especially in relation to designers and project leaders. The analysis of semi-structured interviews with museum professionals showed exhibition production at museums comprise two models: A) curator-driven, and B) manager-driven. In Model A, the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The Latvian permanent exhibition has a much wider time frame, and it has been set up years earlier than the comparable Estonian permanent exhibition. 2000], today practice has also shown that, if the curator withdraws, the designer's and project leader's voice can likewise become one-sided [Viau-Courville 2017;Reidla 2020]. Museologist Graham Black [2012: 275] raises the issue of shared authority which must be "underpinned by the understanding that with such authority comes trust -the trust of museum users in the content provided."…”
Section: Introductionmentioning
confidence: 99%
“…The Latvian permanent exhibition has a much wider time frame, and it has been set up years earlier than the comparable Estonian permanent exhibition. 2000], today practice has also shown that, if the curator withdraws, the designer's and project leader's voice can likewise become one-sided [Viau-Courville 2017;Reidla 2020]. Museologist Graham Black [2012: 275] raises the issue of shared authority which must be "underpinned by the understanding that with such authority comes trust -the trust of museum users in the content provided."…”
Section: Introductionmentioning
confidence: 99%
“…Others emphasized the changing role and enduring importance of curators in museums (Ay el e Durand, 2018;Reidla, 2018). These developments also follow renewed interest in the shifting roles of museum curators and curatorial leadership (Ewin & Ewin, 2016;Gray, 2015;Macdonald & Morgan, 2019;McCall & Gray, 2014;O'Neil, 2016;Paquette, 2015;Reidla, 2020;Tobelem, 2017: 117-120). These two modelsmanagerial and traditional curatorshipare by no means mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%